Pengembangan Kompetensi Sosial Guru Dalam Pelaksanaan Pembalajaran - Jutela, Jutela; Triposa, Reni; Arifianto, Yonatan alex (Sekolah Tinggi Teologi Kanaan Nusantara, 2024)
Developing teacher competency is the ability that teachers have in carrying out learning and delivering material to students so that students can understand all existing learning, become professional teachers who have the ability to teach, have lots of ideas and are creative when in class, using a way of delivering material. It is good for a teacher to develop competence to become a professional teacher in his field. The author used a descriptive qualitative method with a literature study approach in this study. The description in this study concludes the development of teachers' social competence in the process of implementing learning. This is done to develop teachers' social competence in the learning process so that they can be more effective in delivering material to students.AbstrakPengembangan kompetensi guru merupakan kemampuan yang dimiliki guru dalam melaksanakan pembelajaran dan penyampaian materi kepada siswa sehingga siswa dapat memahami setiap pembelajaran yang ada, menjadi guru yang profesional mempunyai kemampuan dalam mengajar, memiliki banyak ide-ide dan kreatif ketika didalam kelas, dengan cara penyampaian yang materi yang baik perlunya seorang guru dalam mengembangkan kompetensi untuk menjadi guru yang profesional dalam bidangnya. Penulis menggunakan metode kualitatif deskritif dengan pendekatan studi pustaka dalam kajian ini. uraian dalam kajian ini menyimpulkan pengembangan kompetensi sosial guru dalam proses pelaksanaan pembelajaran. Hal ini dilakukan untuk mengembangkan kompetensi sosial guru terhadapat proses pelaksanaan pembelajaran agar dapat lebih efektif dalam menyampaikan materi kepada siswa.